Detecting direct oral anticoagulants in trauma patients using liquid chromatography–mass spectrometry: A novel approach to medication reconciliation. Issue 4 (30th April 2020) - Jayaraman, Sudha; DeAntonio, Jonathan H.; Leichtle, Stefan W.; Han, Jinfeng; Liebrecht, Loren; Contaifer, Daniel; Young, Caroline; Chou, Christopher; Staschen, Julia; Doan, David; Kumar, Naren Gajenthra; Wolfe, Luke; et al.
Abstract : BACKGROUND: Accurate medication reconciliation in trauma patients is essential but difficult. Currently, there is no established clinical method of detecting direct oral anticoagulants (DOACs) in trauma patients. We hypothesized that a liquid chromatography–mass spectrometry (LCMS)–based assay can be used to accurately detect DOACs in trauma patients upon hospital arrival. METHODS: Plasma samples were collected from 356 patients who provided informed consent including 10 healthy controls, 19 known positive or negative controls, and 327 trauma patients older than 65 years who were evaluated at our large, urban level 1 trauma center. The assay methodology was developed in healthy and known controls to detect apixaban, rivaroxaban, and dabigatran using LCMS and then applied to 327 samples from trauma patients. Standard medication reconciliation processes in the electronic medical record documenting DOAC usage were compared with LCMS results to determine overall accuracy, sensitivity, specificity, and positive and negative predictive values (PPV, NPV) of the assay. RESULTS: Of 356 patients, 39 (10.96%) were on DOACs: 21 were on apixaban, 14 on rivaroxaban, and 4 on dabigatran. The overall accuracy of the assay for detecting any DOAC was 98.60%, with a sensitivity of 94.87% and specificity of 99.05% (PPV, 92.50%; NPV, 99.37%). The assay detected apixaban with a sensitivity of 90.48% and specificity of 99.10% (PPV, 86.36%; NPV 99.40%). There were three false-positive results and two false-negative LCMS results for apixaban. Dabigatran and rivaroxaban were detected with 100% sensitivity and specificity. CONCLUSION: This LCMS-based assay was highly accurate in detecting DOACs in trauma patients. Further studies need to confirm the clinical efficacy of this LCMS assay and its value for medication reconciliation in trauma patients. LEVEL OF EVIDENCE: Diagnostic Test, level III.